2003
DOI: 10.1073/pnas.1037651100
|View full text |Cite
|
Sign up to set email alerts
|

Substoichiometric shifting in the plant mitochondrial genome is influenced by a gene homologous to MutS

Abstract: The plant mitochondrial genome is retained in a multipartite structure that arises by a process of repeat-mediated homologous recombination. Low-frequency ectopic recombination also occurs, often producing sequence chimeras, aberrant ORFs, and novel subgenomic DNA molecules. This genomic plasticity may distinguish the plant mitochondrion from mammalian and fungal types. In plants, relative copy number of recombination-derived subgenomic DNA molecules within mitochondria is controlled by nuclear genes, and a ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
253
0
1

Year Published

2003
2003
2013
2013

Publication Types

Select...
5
3
2

Relationship

2
8

Authors

Journals

citations
Cited by 233 publications
(258 citation statements)
references
References 58 publications
4
253
0
1
Order By: Relevance
“…Similarly, but unexpectedly, the signal detected in var2-6 (a nonsense mutation by T-DNA insertion) by Anti-VAR1 was as low as that in var1 alleles (Figure 7A). This finding could not be attributed to the variegation itself, because another variegated mutant, chm1-2, the responsible gene of which is unrelated to FtsH (Abdelnoor et al, 2003), did accumulate the VAR1 signal just like Col. Therefore, we suspected that the lack of VAR2 was accompanied by a loss of VAR1.…”
Section: The Accumulation Of Var1 and Var2 Is Regulated Coordinately mentioning
confidence: 88%
“…Similarly, but unexpectedly, the signal detected in var2-6 (a nonsense mutation by T-DNA insertion) by Anti-VAR1 was as low as that in var1 alleles (Figure 7A). This finding could not be attributed to the variegation itself, because another variegated mutant, chm1-2, the responsible gene of which is unrelated to FtsH (Abdelnoor et al, 2003), did accumulate the VAR1 signal just like Col. Therefore, we suspected that the lack of VAR2 was accompanied by a loss of VAR1.…”
Section: The Accumulation Of Var1 and Var2 Is Regulated Coordinately mentioning
confidence: 88%
“…Cloning of CHM revealed that it encodes a gene homologous with Escherichia coli MutS, which is involved in mismatch repair and DNA recombination (Abdelnoor et al, 2003). The investigators have proposed that CHM may be required for recombination or replication and, therefore, that mutation could result in modulation of the copy number of particular molecules (Mackenzie, 2004).…”
Section: Fertility Restoration Through Mtdna Alterationmentioning
confidence: 99%
“…Under some conditions, however, the DNA-repair machinery is unable to cope with all DNA damage and non-conservative repairs occur (Abdelnoor et al, 2003;Cappadocia et al, 2010;Kwon et al, 2010;Maré chal et al, 2009;Shedge et al, 2007). Whirly proteins are negative regulators of a non-conservative repair pathway named microhomology-mediated break-induced replication (MMBIR; Maré chal et al, 2009;Cappadocia et al, 2010).…”
Section: Introductionmentioning
confidence: 99%